2022
DOI: 10.1038/s41598-022-24137-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting arginase-1 exerts antitumor effects in multiple myeloma and mitigates bortezomib-induced cardiotoxicity

Abstract: Multiple myeloma (MM) remains an incurable malignancy of plasma cells despite constantly evolving therapeutic approaches including various types of immunotherapy. Increased arginase activity has been associated with potent suppression of T-cell immune responses in different types of cancer. Here, we investigated the role of arginase 1 (ARG1) in Vκ*MYC model of MM in mice. ARG1 expression in myeloid cells correlated with tumor progression and was accompanied by a systemic drop in ʟ-arginine levels. In MM-bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We have previously shown in healthy rats [ 16 ] and mice [ 12 ] that bortezomib induced LV systolic dysfunction that was most pronounced after the first doses of the drug and gradually resolved both with continuation of therapy and after its discontinuation [ 16 ]. Moreover, it was rather mild and of unlikely clinical significance in a healthy subject.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown in healthy rats [ 16 ] and mice [ 12 ] that bortezomib induced LV systolic dysfunction that was most pronounced after the first doses of the drug and gradually resolved both with continuation of therapy and after its discontinuation [ 16 ]. Moreover, it was rather mild and of unlikely clinical significance in a healthy subject.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have already shown that MM is characterized by increased arginase activity [ 12 ] and ʟ-arginine is an essential substrate for NO production [ 30 ], we tested if an arginase inhibitor improves NO-mediated endothelial function through preservation of ʟ-arginine supply for NO synthesis. However, OAT-1746 only mildly increased plasma nitrite concentrations in healthy and MM mice, slightly improved endothelial function in healthy mice (only bradykinin response), and even tended to reduce it in MM animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations